INSILICO METHOD FOR PREDICTION OF MAXIMUM BINDING AFFINITY AND LIGAND – PROTEIN INTERACTION STUDIES ON ALZHEIMER’S DISEASE - Baskaran, Karthika Perampattu; Arumugam, Arunagiri; Kandasamy, Ruckmani; Alagarsamy, Shanmugarathinam (International Journal of Research -GRANTHAALAYAH, 2020)
The aim of this study is to perform the molecular docking, identifying the drug likeness, ADME properties of drugs, Ligand-Protein interactions using different softwares. Due to the excess activity of Acetylcholinesterase, plaque formation and tau protein aggregation in the brain is the main cause for the Alzheimer’s disease. The interaction of Donepezil, Rivastigmine and Chlorzoxazone against AChE protein crystal structure (4EY5, 4EY6, 4EY7) using molecular docking were analyzed. Docking results of Rivastigmine and Chlorzoxazone were compared with Donepezil (widely used drug for Alzheimer’s disease) to identify the binding affinity. To verify whether Chlorzoxazone could act similarly as effective drug of Donepezil and also finding in which protein structure, ligands could bind effectively were employed using BIOVIA Discovery Studio software. Among those ligands interaction with all protein structure, 4EY7 on Rivastigmine (-7.1 kcal/mol) exhibits maximum binding affinity. The interactions of three ligands were compared with one another, in that Hydrogen bond formation of Chlorzoxazone and Donepezil with 4EY6 and 4EY7 interacting the similar aminoacids residues (4EY6-ARG165; 4EY7-ASP74) were studied using insilico studies .